(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the main challenges encountered in teaching English for Specific Purposes (ESP) within engineering education and proposes practical solutions to improve learning outcomes. In the era of globalization, English has become the dominant language of science, technology, and professional communication. Engineering students are required not only to understand general English but also to master technical terminology, professional discourse, and communicative competence relevant to their field.